2010
DOI: 10.3109/09286580903450338
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Presentation of Cataracts in Children: Are they Worth Operating Upon?

Abstract: Surgery for cataracts with delayed presentation helps to regain functional vision, which can be used for navigation and low vision aids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 19 publications
(21 reference statements)
5
34
0
Order By: Relevance
“…This is notable in the context of the high drop-out rates previous studies 1820 have reported when following patients treated for long-standing cataracts. There was significant improvement in BCVA at 6 months follow-up for a majority of the children.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This is notable in the context of the high drop-out rates previous studies 1820 have reported when following patients treated for long-standing cataracts. There was significant improvement in BCVA at 6 months follow-up for a majority of the children.…”
Section: Discussionmentioning
confidence: 76%
“…Some studies suggest poor visual outcomes in children with bilateral congenital cataracts even with a delay of just a little over 1 year. 17 On the other hand, studies from western India, 18 Nepal 19 and Tanzania 20 report visual improvement in cases of delayed cataract treatment. Some of the apparent contradictions across these studies stem from their small sample sizes, variable definitions of `delay' and the inclusion of both early and late-onset cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…However, following the intervention, the child can utilize the residual vision and use low vision aids to improve his/her quality-of-life 46. As a result, for disabled children especially in Group 3 countries, maximum efforts should be dedicated to allocate proper resources in identifying treatable blindness even if such conditions present in the late stages or are initially detected at an older age.…”
Section: Measures To Address the Problemmentioning
confidence: 99%
“…29 On the other hand, studies from western India, 30 Nepal, 31 and Tanzania, 32 report visual improvement in cases of delayed cataract treatment. Some of the apparent contradictions across these studies stem from their small sample sizes, variable definitions of 'delay' and the inclusion of both early and late-onset cataracts.…”
Section: Discussionmentioning
confidence: 99%